A modular system to evaluate the efficacy of protease inhibitors against HIV-2. - Mohamed Mahdi; Krisztina Matúz; Ferenc Tóth; József Tőzsér (PLoS ONE)
The human immunodeficiency virus (HIV) protease is a homodimeric aspartyl protease that is crucial for the viral life-cycle, cleaving proviral polyproteins, hence creating mature protein components that are required for the formation of an infectious virus. With diagnostic measures and clinically used protease inhibitors focusing on HIV-1, due to its higher virulence and prevalence, studies of the efficacy of those inhibitors on HIV-2 protease remain widely lacking. Utilizing a wild-type HIV-2 vector backbone and cloning techniques we have developed a cassette system where the efficacy of clinically used protease inhibitors can be studied for various serotypes of HIV-2 protease both in enzymatic and cell culture assays. In our experiments, optimization of the expression protocol led to a relatively stable enzyme, for cell culture assays, the efficiency of transfection and transduction capability of the modified vector was tested and was not found to differ from that of the wild-type, moreover, a 2nd generation protease inhibitor was used to demonstrate the usefulness of the system. The combination of assays performed with our cassette system is expected to provide an accurate measure of the efficacy of currently used; as well as experimental protease inhibitors on HIV-2.